Pengaruh Quality Of Work Life dan Komitmen Organisasional terhadap Kinerja Karyawan dengan Organizational Citizenship Behavior sebagai variabel intervening pada hotel Amanda Hills Bandungan - Ismadiwati Rahma; Widiartanto Widiartanto (Jurnal Ilmu Administrasi Bisnis, 2016)
This study is about the Influence Quality Of Work Life and Organizational Commitment on Employee Performance With Organitational Citizenship Behavior As an intervening variable At Hotel Amanda Hills Bandungan. This study was conducted to determine the factors that affect employee performance and test variables Organitational Citizenship Behavior As an intervening variable.This type of research is explanatory research study or explanation. The population in this study were employees of Hotel Amanda Hills Bandungan as many as 40 people. Sampling technique uses the entire population census is used as a sample so that the sample of 40 people. Methods of data collection using questionnaires, while data analysis technique used is the test of validity, reliability, t test, F test test, the coefficient of determination, regression analysis and path analysis. Calculations in this study using SPSS for windows.The calculations show that there are significant Quality Of Work Life and Organizational Commitment on Organizational Citizenship Behavior and Performance Employees, the result of calculation of the path analysis showed that mediates the effect of Organizational Citizenship Behavior Quality of Work Life of the performance and do not mediate the effect of the influence of Organizational Commitment to Performance. Advice given is the company should maintain Organizational Citizenship Behavior problems because it has a large palng influence and improve organizational commitment because it has little influence.